Relative and combined Effects of Ethanol and Hepatitis C Virus Infection on Serum Interleukin-17 Levels - Emilio González-Reimers; Candelaria Martín-González; Geraldine Quintero-Platt; Lucía Romero-Acevedo; Onán Pérez- Hernández; Elisa Espelosín-Ortega; María José de-; Antonieta González-Díaz; Francisco Santolaria-Fernández (Archives of Hepatitis Research - Peertechz Publications, 2017)
Background: Interleukin-17 (IL-17) is involved in neutrophil recruitment and may contribute to the progression from fatty liver to steatohepatitis. Its role in alcoholics and in HCV-infected patients is not clear, lower- or higher-than normal values having been reported. Aim: To study the behavior of IL-17 among alcoholics with or without Hepatitis C virus infection (HCV), given the frequent association of both entities and the apparently opposite results reported in these two groups of patients. Results: Among 96 alcoholics, 10 with co-existing HCV infection, 15 non-alcoholic HCV-infected patients and 21 controls, IL-17 showed signifi cant differences between patients (median=2.76; IQ=0.85- 5.50) and controls (median=0.50; IQ= 0.30-1.54; Z=3.06, p=0.002). Also, IL-17 was signifi cantly different when the sample was classifi ed in 4 groups (alcoholics without HCV infection, alcoholics with HCV infection, non-alcoholics, HCV infected patients, and controls (KW= 11.86; p=0.008). Main findings: By two way variance analysis we disclosed that both hepatitis C (F=7.36; p=0.008) and alcohol consumption (F=6.16; p=0.014) exerted signifi cant effects on IL-17, a negative interaction  existing between both variables (F=4.97; p=0.028). Inverse correlations were observed between left leg fat and IL-17 (ρ= -0.28; p= 0.009). Patients with IL-17 over the median showed less trunk fat than those with IL-17 below the median (Z=2.072; p=0.038), and also less total body fat (Z=1.99; p=0.046). No relations were observed between IL-17 and viral load, ethanol consumption or liver function impairment. Conclusion: Ethanol and HCV infection lead to increased IL-17 levels, similar to what is observed when both factors coexist. An inverse relationship exists between body fat and IL-17. Brief Summary: Interleukin-17 is a cytokine produced by lymphocytes involved in neutrophil recruitment that may have a role in the progression from fatty liver to steatohepatitis. Its role in alcoholics and in HCV-infected patients is controversial. We here report higher IL-17 levels in alcoholic and HCVinfected patients. Additionally, we also describe an inverse relationship between IL-17 levels and fat mass which supports an inhibitory role of this cytokine on adipogenesis. To our knowledge, no other study has analysed the relative and combined effects of HCV and ethanol on IL-17 levels, as we have done in this study.